Interstitial lung disease is a major characteristic of anti-KS associated ant-synthetase syndrome - Yongpeng Ge; Sizhao Li; Shanshan Li; Linrong He; Xin Lu; Guochun Wang (SAGE Publishing, 2020)
Background: Anti-KS autoantibodies are rare myositis-specific autoantibodies that have been described to target asparaginyl-transfer RNA synthetase. Methods: Here, we review the published literature on critical issues concerning the detection of anti-KS antibodies and the clinical features associated with their presence. Results: Seven articles are reviewed, in all of which immunoprecipitation was employed for the detection of anti-KS antibodies. A total of 47 patients were included; the ratio of females to males was 1.9:1. In total, 46 (98%) of these patients had interstitial lung disease (ILD), which was the sole manifestation in half (50%) of them. Pulmonary pathology revealed 7 (27%) with usual interstitial pneumonia, and 16 (62%) with non-specific pneumonia. Arthritis was present in about one-quarter (26%) of patients, and the incidence of Raynaud's phenomenon and mechanic's hands was 19% and 32%, respectively. However, manifestations of myositis were rare (9%). In addition, three (11%) patients had malignant tumors. Most patients responded to glucocorticoid therapy. Conclusions: Identifying anti-KS in patients with ILD may be useful for treatment, but reliable practical detection is needed. Furthermore, clinicians need to be aware of the possible presence of anti-KS antibodies in patients with ILD, either isolated or in combination with myositis.